2014
DOI: 10.1185/03007995.2014.946126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the first oxycodone once daily prolonged release tablet in moderate to severe chronic pain: a randomized, double-blind, multicenter, cross-over, non-inferiority study to investigate efficacy and safety in comparison with an established oxycodone twice daily prolonged release tablet

Abstract: (2014) Clinical evaluation of the first oxycodone once daily prolonged release tablet in moderate to severe chronic pain: a randomized, double-blind, multicenter, cross-over, non-inferiority study to investigate efficacy and safety in comparison with an established oxycodone twice daily prolonged release tablet, Current Medical Research and Opinion, 30:11, 2365-2375, DOI: 10.1185/03007995.2014 AbstractObjective:The first oxycodone once daily (OOD) has been developed and after successful pharmacokinetic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It could be assumed that OOD leads to comparable efficacy and safety and is therefore exchangeable when administered at the same total daily dose as OTD. This finding could be confirmed by results of a recent trial in patients [ 28 ]. The randomized, double-blind, cross-over trial in patients with malignant and nonmalignant moderate to severe chronic pain showed that OOD is at least equivalent to OTD regarding therapeutic efficacy and safety.…”
Section: Discussionsupporting
confidence: 75%
“…It could be assumed that OOD leads to comparable efficacy and safety and is therefore exchangeable when administered at the same total daily dose as OTD. This finding could be confirmed by results of a recent trial in patients [ 28 ]. The randomized, double-blind, cross-over trial in patients with malignant and nonmalignant moderate to severe chronic pain showed that OOD is at least equivalent to OTD regarding therapeutic efficacy and safety.…”
Section: Discussionsupporting
confidence: 75%
“…(Kokki et al 2004), intranasally (i.n.) (Takala et al 1997;Dale et al 2002), subcutaneously (s.c.) (Kokubun et al 2014), bucally (Kokki et al 2004), rectally (Tegon et al 2009;Li et al 2011), epidurally (Kokki et al 2014), and orally (Mandema et al 1996;Bass et al 2012;Mundin et al 2012;Kim et al 2015) using immediate release (IR) solutions and immediate-and controlled-release tablets to diverse disease populations for the treatment of acute, and chronic nonmalignant pain and cancer pain (Hanks et al 2001;Radbruch and Nauck 2002;Lux et al 2014;Mehta et al 2014;Stessel et al 2014;Poelaert et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The reported mean/median ages of the participant populations in the studies ranged from 45 years to 68.8 years. Eleven of the studies were crossover trials (published in 16 articles),12 16–30 and 12 were parallel-group trials (published in 13 articles),13 31–42 with 8 of the studies conducted in the USA,16 17 20 21 29 30 33 35 36 39 2 in Canada,18 22 3 in Finland,23–25 3 in China,13 40 42 3 in Italy31 34 41 and one each in Germany/Poland/Switzerland,12 Australia,28 Brazil,27 the UK37 38 and Japan/Korea 32. The length of the trials ranged from single-dose treatment to 1 year, and the studies reported the following comparisons:

CR oxycodone versus IR oxycodone29 30 33 36 39

CR oxycodone versus extended-release (ER) oxycodone12

CR oxycodone versus CR morphine,18 19 23 24 27 31 34 35 37 38 41 42 with one of these studies including a further two arms of transdermal (TD) buprenorphine and TD fentayl,31 and one of the studies comparing two different brands of slow-release morphine to CR oxycodone42

CR oxycodone versus CR hydromorphone22

CR oxycodone versus ER hydromorphone13

CR oxycodone versus ER oxymorphone20 21

CR oxycodone versus ER tapentadol32

CR oxycodone versus TD fentanyl31 40

CR oxycodone versus TD buprenorphine31

intravenous oxycodone versus rectal oxycodone28

intravenous oxycodone followed by IR oxycodone versus intravenous morphine followed by IR morphine25 26

intramuscular (IM) oxycodone vs oral oxycodone16

IM oxycodone versus IM morphine versus IM codeine 17

…”
Section: Resultsmentioning
confidence: 99%
“…We limited imputation of missing data to the imputation of missing SDs, either by calculating the SD if enough information was available or by using SDs from similar samples or studies, both according to the methods outlined by Higgins and Green 11. We only imputed SDs for pain intensity for Lux et al ,12 which were not reported for the subgroup of participants with malignant pain, by using the reported SDs for the whole sample of participants with either malignant (n=31) or non-malignant pain (n=15), and for Yu et al 13 for the primary outcome of the study ‘mean pain at its worst in the past 24 hours’ by using the SDs for the same outcome measured at baseline in the full analysis set. It was not possible to assess the impact of missing data in sensitivity analyses due to the low number of included studies within each comparison.…”
Section: Methodsmentioning
confidence: 99%